2016
DOI: 10.1038/jp.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of neonatal transports in California

Abstract: As many neonates receive transport within the first week after birth, there may be opportunities for quality improvement activities in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Akula et al (2016) reported on neonatal transport cases in California, USA. They found that the transported infants were more likely to be male, and that nearly one third were diagnosed with congenital malformations [ 9 ]. In our study, care and transport by HEMS and EMS crews in Poland were required more often in cases of male newborns, with the most common diagnoses involving congenital malformations, and especially congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Akula et al (2016) reported on neonatal transport cases in California, USA. They found that the transported infants were more likely to be male, and that nearly one third were diagnosed with congenital malformations [ 9 ]. In our study, care and transport by HEMS and EMS crews in Poland were required more often in cases of male newborns, with the most common diagnoses involving congenital malformations, and especially congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…According to Akula et al (2016), helicopters were most often used for emergency transport, compared to other modes of transport and mission types [ 9 ]. In turn, our study demonstrated that emergency response was more often provided by Polish Medical Air Rescue teams in cases where the diagnosis involved respiratory failure, sudden cardiac arrest, and other health problems, while rescue transport and patient transfer flights were carried out most often in cases of newborns with congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This network serves to facilitate the transport of critically ill infants to NICUs offering a higher level of care that are better able to meet their needs [12]. These transports are extremely heterogeneous with respect to gestational age at birth, postnatal age at transport and clinical status [16]. The CPeTS collects comprehensive neonatal transport data that are linked to the CPQCC database.…”
Section: Study Population and Data Sourcementioning
confidence: 99%